2005
DOI: 10.1021/jf051197n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Acrylamide Formation and Elimination during Heating of an Asparagine−Sugar Model System

Abstract: The kinetics of acrylamide (AA) was analyzed by heating a simple model system consisting of asparagine and glucose, fructose, or sucrose (0.01 M, pH 6) at temperatures between 140 and 200 degrees C. The AA concentration appeared to be the net result of simultaneous formation and elimination. A general kinetic model describing the AA yield was identified, and kinetic parameters were obtained by nonlinear regression on the nonisothermally derived data. On the basis of kinetic parameters, the AA formation appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 26 publications
5
100
0
4
Order By: Relevance
“…Indeed, at 200°C the maximum acrylamide amount (4 ppm) is reached after 7 min, this result being slightly different from those of the literature. Indeed, Claeys, De Vleeschouwer, and Hendrickx (2005b) found, in the same conditions, a maximum yield of acrylamide around 3 ppm after 10 min of treatment (200°C). This could be explained by the difference of the temperature-time profiles.…”
Section: Kinetics Of Acrylamide Formationmentioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, at 200°C the maximum acrylamide amount (4 ppm) is reached after 7 min, this result being slightly different from those of the literature. Indeed, Claeys, De Vleeschouwer, and Hendrickx (2005b) found, in the same conditions, a maximum yield of acrylamide around 3 ppm after 10 min of treatment (200°C). This could be explained by the difference of the temperature-time profiles.…”
Section: Kinetics Of Acrylamide Formationmentioning
confidence: 56%
“…2). De Vleeschower, van der Plancken, van Loey, and Hendrickx (2008) found a maximum concentration of acrylamide around 2 ppm after 10 min using the same device as Claeys et al (2005b) but the time-temperature profiles were not shown. For the rest of the study all experimentations were performed at 200°C.…”
Section: Kinetics Of Acrylamide Formationmentioning
confidence: 99%
“…Evaporation and/or polymerization are assumed to be the main causes of ACR decrease in the control as reported by others (i.e. Adams, Hamdani, Lancker, Méjri, & Kimpe, 2010;Claeys, de Vleeschouwer, & Hendrickx, 2005).…”
Section: Resultsmentioning
confidence: 78%
“…Traditionally, researchers have used glucose-asparagine model systems to evaluate the kinetics of ACR formation/elimination under different conditions (Claeys et al, 2005;Knol et al, 2005). A dynamic system with ACR precursors (glucose þ asparagine) was designed, and formation and elimination of ACR took place simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…AA has been found in numerous carbohydrate-rich foods after being fried, baked, or roasted at a temperature higher than 120 C. The well-accepted mechanism of AA formation in foods is the asparagine-reducing sugars (usually fructose and glucose) pathway accompanied by the Millard reaction, wherein an intermediate Schiff base is first formed, followed by AA formation via the Strecker pathway or N-glycoside pathway (Claeys, De Vleeschouwer, & Hendrickx, 2005;Mottram, Wedzicha, & Dodson, 2002;Stadler et al, 2002). Another pathway that has been reported is the acrolein pathway after organic acid decarboxylation (Medeiros Vinci, Mestdagh, & De Meulenaer, 2012;Yaylayan & Stadler, 2005).…”
Section: Existence and Formation Of Aa In Foodsmentioning
confidence: 99%